Analysis of the Influence of User Experience and Product Quality on Repurchase Intention with User Satisfaction as an Intervening Variable Uniqlo App - Lumbantoruan, Ronaldo Fransiskus (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The objective of the research is to analyze the effects of the variables user experience and product quality on repurchase intention with user satisfaction as an intervening variable uniqlo app. The research uses quantitative approach with associative design. The data consist of primary and secondary data gathered by conducting documentary study and questionnaire, using Likert Scale. The samples are 180 people in medan city regency with the minimum age of 18, taken by using accidental sampling technique. The gathered data are analyzed by using SmartPLS software. The result of the research shows that, directly, user experience and product quality have a positive and significant effect on user satisfaction. The user experience and product quality variables directly have a positive and significant effect on repurchase intention. The user satisfaction variable has a negative and significant effect on repurchase intention. Indirectly, user experience and product quality through user satisfaction have a negative and significant effect on repurchase intention.